Teaching Knowledge Synthesis Methodologies in a Higher Education Setting: A Scoping Review of Face-to-Face Instructional Programs - Premji, Zahra; Hayden, K. Alix; Rutherford, Shauna (Evidence Based Library and Information Practice, 2021)
Background – Knowledge synthesis (KS) reviews are increasingly being conducted and published. Librarians are frequently taking a role in training colleagues, faculty, graduate students, and others on aspects of knowledge syntheses methods.Objective – In order to inform the design of a workshop series, the authors undertook a scoping review to identify what and how knowledge synthesis methods are being taught in higher education settings, and to identify particularly challenging concepts or aspects of KS methods.Methods – The following databases were searched: MEDLINE, EMBASE & APA PsycInfo (via Ovid); LISA (via ProQuest); ERIC, Education Research Complete, Business Source Complete, Academic Search Complete, CINAHL, Library & Information Science Source, and SocIndex (via EBSCO); and Web of Science core collection. Comprehensive searches in each database were conducted on May 31, 2019 and updated on September 13, 2020. Relevant conferences and journals were hand searched, and forward and backward searching of the included articles was also done. Study selection was conducted by two independent reviews first by title/abstract and then using the full-text articles. Data extraction was completed by one individual and verified independently by a second individual. Discrepancies in study selection and data extraction were resolved by a third individual.Results – The authors identified 2,597 unique records, of which 48 full-text articles were evaluated for inclusion, leading to 17 included articles. 12 articles reported on credit courses and 5 articles focused on stand-alone workshops or workshop series. The courses/workshops were from a variety of disciplines, at institutions located in North America, Europe, New Zealand, and Africa. They were most often taught by faculty, followed by librarians, and sometimes involved teaching assistants.Conclusions – The instructional content and methods varied across the courses and workshops, as did the level of detail reported in the articles. Hands-on activities and active learning strategies were heavily encouraged by the authors. More research on the effectiveness of specific teaching strategies is needed in order to determine the optimal ways to teach KS methods.